2014
DOI: 10.1007/s12149-014-0931-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 11C-4′-thiothymidine, 11C-methionine, and 18F-FDG PET/CT for the detection of active lesions of multiple myeloma

Abstract: PurposeThe aims of this study were to evaluate the possibility of using 11C-methionine (11C-MET) and 11C-4′-thiothymidine (11C-4DST) whole-body PET/CT for the imaging of amino acid metabolism and DNA synthesis, respectively, when searching for bone marrow involvement in patients with multiple myeloma (MM) and to compare these findings with those for 18F-FDG PET/CT and aspiration cytology.MethodsA total of 64 patients with MM, solitary plasmacytoma, monoclonal gammopathy of undetermined significance, or an unsp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 26 publications
6
26
0
Order By: Relevance
“…Once [11C]-4DST is incorporated into DNA, de-phosphorylation occurs relatively rarely, unlike [18 F]-FLT. This has also been shown in a study of MM patients in which [11C]-4DST showed more positive findings per patient than [18 F]-FDG-PET, particularly in patients with low numbers of bone marrow plasma cells (Table 2B) [25]. …”
Section: Target Mechanism In Nuclear Imagingsupporting
confidence: 67%
See 2 more Smart Citations
“…Once [11C]-4DST is incorporated into DNA, de-phosphorylation occurs relatively rarely, unlike [18 F]-FLT. This has also been shown in a study of MM patients in which [11C]-4DST showed more positive findings per patient than [18 F]-FDG-PET, particularly in patients with low numbers of bone marrow plasma cells (Table 2B) [25]. …”
Section: Target Mechanism In Nuclear Imagingsupporting
confidence: 67%
“…Due to the active protein synthesis by the malignant plasma cells, this might also be a useful tracer for MM. In several studies, [11C]-MET was compared with [18 F]-FDG-PET (Table 2B) [25, 26]. Compared to [18 F]-FDG-PET, more lesions were detected with [11C]-MET, especially when a low number of aberrant plasma cells were present in the bone marrow (<30 %) [25].…”
Section: Target Mechanism In Nuclear Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…The main findings of the study were the following: firstly, the number of equivocal lesions observed using 18 F-FDG was larger compared to using 11 C-methionine or 11 C-4DST both before and after therapy. Secondly, 11 C-methionine and 11 C-4DST were superior to 18 F-FDG in clearly detecting skull lesions because of their low physiological accumulation in the brain [48].…”
Section: C-methioninementioning
confidence: 99%
“…Okasaki et al conducted a prospective study in an undeveloped medical field: a comparative study of the diagnostic evaluation of multiple myeloma (MM) using three different PET tracers, 18 F-fluorodeoxyglucose (FDG), an amino acid tracer 11 C-methionine (MET), and a tumour proliferation tracer 11 C-4′-thiothymidine (4DST) which has been recently introduced in Japan [1]. The progression of MM from care-not-required premalignant conditions, including monoclonal gammopathy of undetermined significance (MGUS) and smouldering MM (SMM), to care-required MM with end-stage organ damage requires clinical evaluation, but the diagnostic imaging for this purpose has not been established.…”
Section: Oncologymentioning
confidence: 99%